Development and preliminary psychometric evaluation of the Psychological Safety Perception scale: an observational study among community pharmacists - Jocić, Dragana (Vojnosanitetski pregled, 2026)
Background/Aim. Measuring psychological safety in the workplace is essential for creating an environment where individuals feel safe expressing themselves, thereby promoting optimal patient care. The aim of the study was to develop a reliable and concise scale with preliminary psychometric properties to measure psychological safety in community pharmacies. Methods. After scale development through content and face validity, a cross-sectional study was conducted in which data were collected from 216 community pharmacists. A test-retest component was subsequently performed on 32 pharmacists at baseline and after three months to assess the temporal stability of the scale. Exploratory factor analysis (EFA), confirmatory factor analysis (CFA), the Wilcoxon signed-rank test, and Spearman’s correlation coefficient (ρ) were used to evaluate the scale’s reliability, construct validity, and stability. Results. The scale was developed through multiple iterations: Version 1 (32 items), Version 2 (26 items), and Version 3 (15 items), all of which demonstrated high content and face validity (indices > 0.80) and internal consistency (Cronbach’s alpha = 0.92). Version 4 (10 items) was established through CFA, which suggested excluding certain items, resulting in excellent reliability (Cronbach’s alpha = 0.89) and fit parameters: χ2(35) = 65.81; p < 0.001; goodness of fit index – GFI = 0.94; comparative fit index – CFI = 0.97; Tucker-Lewis index – TLI = 0.96; root mean square error of approximation – RMSEA = 0.064; standardized root mean square residual – SRMR = 0.040. During psychometric evaluation, EFA revealed a one-factor structure, with the primary component explaining nearly 50% of the variance. The Wilcoxon signed-rank test indicated no significant difference in mean scores between baseline [mean = 50.72, standard deviation (SD) = 12.93] and retest after three months (mean = 50.69, SD = 12.59). Additionally, Spearman’s correlation coefficients showed strong correlations between baseline and three-month scores (ρ = 0.994; p < 0.001). Conclusion. The findings indicate promising preliminary psychometric properties, supporting the use of the developed scale to assess psychological safety perceptions in community pharmacies. However, further validation, including criterion, convergent, and discriminant validity testing, is required.